The New Approach of Intercalation Material for The Application of Rechargeable Lithium Batteries - Shi-Jie Wen; Xiao-Tian Yin; L. Nazar (Active and Passive Electronic Components)
A new approach of lithium electrochemical (de)intercalation material has been put forward. This approach requires a two-compound (physically or chemically) composite in which one is a chemically and electrochemically stable and porous (tunnel, cage, layer, etc.) compound such as clay or zeolite, and the other is a chemically and electrochemically stable and metallic compound such as graphite, metal powder or black carbon. Neither does the redox couple in this composite absolutely exist nor does the redox reaction, which is associated with electrochemical charge and discharge processes when this composite is used as an cathodic electrode in a lithium battery cell. In this paper, we show the results of the lithium electrochemical intercalation process in both black carbon-mixed zeolite and clay electrodes. In these solid electrodes, black carbon serves to delocalize (transport) electrons for balancing the charges while zeolite and clay offer the neutrally reversible sites for lithium ions. This approach can hopefully become a guide for the designing of new intercalation material and so will be very important in the application of the lithium rechargeable battery.